An approach to the sizing of electric motors devoted to aerospace propulsion systems. Issue 5 (19th August 2014) - Bouzidi, Ikhlas; Bianchi, Nicola; Masmoudi, Ahmed; Sykulski, Jan; Masmoudi, Ahmed
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This paper deals with the design and optimization of PM synchronous motors devoted to aeronautic applications. Design/methodology/approach A design approach as well as a performance investigation, based on two-dimensional finite element analysis of selected electromagnetic and thermal features, are applied to chosen PM synchronous machine topologies which differ by their number of phases. Findings It has been found that the initial set of geometrical parameters does not fulfill the torque/weight compromise required by a ronautic applications since it leads to an average temper- ature rise higher than the authorized limit(class H: 155K). Therefore, the sizing has been rethought in an attempt to meet the constraints of the considered application. Research limitations/implications Several continuations of the developed works shall be treated in the future, such as: (i) the prototyping of the designed machines, (ii) extending the optimization procedure to the whole drive including the motor and the associated static converter, and (iii) the synthesis and implementation of a dedicated control strategy with a suitable emulation of the load. Practical implications The studied machines could be integrated in aerospace propulsion systems. Originality/value The paper develops a design procedure of PM synchronous motors dedicated to aerospace applications where the compromise between torque/weight/temperature represents a crucial design challenge.